Subjective sleep quality, unstimulated sexual arousal, and sexual frequency - Costa, Rui; Costa, David; Pestana, José (Sleep Science, 2017)
Introduction REM sleep deprivation increases unstimulated erections in rats, and total sleep deprivation increases erections during audiovisual sexual stimulation in men, but the effects of sleep problems on human unstimulated sexual arousal are unknown.Objective We examined the associations of subjective sleep quality with unstimulated sexual arousal, satisfaction with sex life, and sexual frequency and desire over the past month.Methods 275 Portuguese (169 women) reported their anxiety, sexual arousal and sexual desire during a resting state, and completed the Pittsburgh Sleep Quality Index, the sexual satisfaction subscale of the LiSat scale, the Desire dimensions of the Female Sexual Function Index (women only) and International Index of Erectile Function (men only). They additionally reported how many days in the past month they engaged in penile-vaginal intercourse, noncoital sex, and masturbation. Salivary testosterone (T) was assayed by luminescence immunoassays.Results Poorer sleep quality correlated with greater unstimulated sexual arousal in men with higher T levels and in women with higher T levels not taking oral contraceptives. In women with lower T, poorer subjective sleep quality correlated with greater sexual dissatisfaction. In both sexes, sleep quality was uncorrelated with sexual desire and sexual frequency over the past month.Discussion Consistently with other studies in humans and animals, the findings are congruent with the notion that lack of sleep can increase sexual arousal, but not sexual frequency. T might play a role in the sexual arousal caused by lack of appropriate sleep.
Keywords: Sleep; Coitus; Sexual Dysfunctions, Psychological